(untitled) (Research, Society and Development, 2022)
This research analyzed the perception of 42 higher education students about Environmental Education (EE) activities in environmental management and explored spontaneous conceptions about an urban green park. Data were obtained in 2016 through a questionnaire based on the Free Word-Association Test methodology and analyzed by the Collective Subject Discourse. In the students conception, the importance of EE as a process of environmental management is imperative, being seen as an instrument or tool for raising awareness among the population. As a management instrument, EE seems to assume a technical and disciplining character, and as a tool to raise awareness among the population, it reflects the utilitarian model of society, favorable to the principles of a conservative EE. The association test showed that the studied urban green park was represented mainly by the words “degradation” and “natural,” showing dichotomous and biologizing trends. The results indicate the need to adopt activities that allow transposing the experiences presented by the students. It will contribute to the construction of a more critical, emancipatory EE that is really focused on the complex environmental agenda.